Yoga for Self-Care and Burnout Prevention Among Nurses. (October 2015) - Alexander, Gina K.; Rollins, Kari; Walker, Danielle; Wong, Lily; Pennings, Jacquelyn
The promotion of self-care and the prevention of burnout among nurses is a public health priority. Evidence supports the efficacy of yoga to improve physical and mental health outcomes, but few studies have examined the influence of yoga on nurse-specific outcomes. The purpose of this pilot-level randomized controlled trial was to examine the efficacy of yoga to improve self-care and reduce burnout among nurses. Compared with controls ( n = 20), yoga participants ( n = 20) reported significantly higher self-care as well as less emotional exhaustion and depersonalization upon completion of an 8-week yoga intervention. Although the control group demonstrated no change throughout the course of the study, the yoga group showed a significant improvement in scores from pre- to post-intervention for self-care ( p < .001), mindfulness ( p = .028), emotional exhaustion ( p = .008), and depersonalization ( p = .007) outcomes. Implications for practice are discussed.